2010
DOI: 10.1007/s10265-010-0317-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen status of litterfall, litter decomposition and soil in even-aged larch, red pine and rigitaeda pine plantations

Abstract: The carbon (C) and nitrogen (N) status in forest ecosystems can change upon establishment of plantations because different tree species have different nutrient cycling mechanisms. This study was carried out to evaluate C and N status of litterfall, litter decomposition and soil in three adjacent plantations consisting of one deciduous (larch: Larix leptolepis) and two evergreen (red pine: Pinus densiflora; rigitaeda pine: P. rigida x P. taeda) species planted in the same year (1963). Both the pine plantations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
3
8
1
Order By: Relevance
“…Ozdemir et al / Forest Systems (2013) 22(2), 214-221 Similar to our results on soil nitrogen with no differences among investigated plots, Kim et al (2010) reported that the soil N concentration and content were not significantly different among the three coniferous plantations in their study. In contrast to C remaining, the N remaining in decomposing larch needle litter showed higher N gains than in either of the pine needle litters because the N in larch needle litter is readily immobilized by microorganisms due to its high concentration compared with pine needle litter (Kim et al, 2010). Added to that, Compton et al (1998) stated that the land use or vegetation type had no significant impacts on soil N concentration.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Ozdemir et al / Forest Systems (2013) 22(2), 214-221 Similar to our results on soil nitrogen with no differences among investigated plots, Kim et al (2010) reported that the soil N concentration and content were not significantly different among the three coniferous plantations in their study. In contrast to C remaining, the N remaining in decomposing larch needle litter showed higher N gains than in either of the pine needle litters because the N in larch needle litter is readily immobilized by microorganisms due to its high concentration compared with pine needle litter (Kim et al, 2010). Added to that, Compton et al (1998) stated that the land use or vegetation type had no significant impacts on soil N concentration.…”
supporting
confidence: 90%
“…For instance, the initial C/N ratios for Pinus pinaster and Pinus nigra for other conifer species are higher than our results (Klemmedson, 1992;Joseâ Moro and Domingo 2000). The C and N distribution of the surface soil layer might reflect differences in the quality and quantity of litter fall inputs, litter decomposition dynamics, and the production and turnover of fine roots, which are the principal pathways for the return of C and N to the soil (Finzi et al, 1998;Wang et al, 2009;Kim et al, 2010). On the other hand, there are many factors which were mentioned in different sections of the manuscript and are mainly effective on soil C/N ratios such as biological activity, nitrogen use efficiency of vegetation and soil organisms, mineralization, leaching or fixation.…”
Section: C/n Ratiocontrasting
confidence: 58%
See 1 more Smart Citation
“…Similarly, C concentration varies significantly among tree components (Bert andDanjon 2006, Zhang et al 2009). The C concentration of needle litter observed in this study was comparable to that of needle litter (510 mg/g) in a 43-year-old red pine plantation in Gyeongnam province, Korea (Kim et al 2010b). …”
Section: Carbon and N Inputs From Litterfall In The Damaged Pine Wiltsupporting
confidence: 72%
“…The study sites have identical macroclimatic conditions and plantation ages. More information about soil, understory vegetation and litter fall of this study site can be found elsewhere (Kim et al 2010).…”
Section: Methodsmentioning
confidence: 99%